The concentrations of bone calcium, phosphorus and trace metal elements in elderly patients with intertrochanteric hip fractures - Lin, Shangjin; Chen, Cong; Cai, Xiaoxi; Yang, Fengjian; Fan, YongQian (Frontiers in Endocrinology, 2022)
Introduction: Trace metal elements may play a crucial role in bone mineralization and metabolism; however, there are little researches on the measurement of trace elements concentration in human bone tissue. Materials and methods: In this study, bone tissue samples from 55 elderly patients (15 males and 40 females) with intertrochanteric hip fractures were collected, and the concentrations of calcium, phosphorus, manganese, iron, copper and zinc in the cortical bone zone, cancellous bone zone, and junction zone between cortical and cancellous bone were determined by Energy-dispersive X-ray fluorescence (EDX). Afterward, the Kruskal-Wallis test was applied to compare the differences of trace element concentrations in the three regions and analyze the correlation between gender and bone trace elements contents. Finally, the Spearman correlation analysis was used to determine the correlation among bone trace elements in different zones and explore the correlation between age, BMI and the concentrations of bone calcium, phosphorus and trace elements in three zones. Results: The Kruskal-Wallis test showed no difference in bone phosphorus concentration among the three regions, while the difference in the concentrations of bone calcium and four metal elements were statistically significant (P＜0.01). Besides, no statistical differences were observed in the concentrations of trace elements among the three regions of elderly male and female patients. Thereafter, the Spearman correlation analysis showed a significant negative correlation between bone calcium and phosphorus in three regions (r=-0.999, -0.95, -0.998, P < 0.01), and a significant positive correlation between trace metal elements in the cancellous bone zone. In the junction zone, BMI had a significant positive correlation with bone calcium content (r=0.347, P=0.009) and a significant negative correlation with the phosphorus content (r=-0.349, P=0.009). Conclusion: Bone calcium and phosphorus were the main components of hydroxyapatite, and the sum of these two elements accounted for the majority of bone mineral salts. Trace metal elements play a crucial role in bone metabolism and specific synergistic interactions. BMI may be related to bone calcium and phosphorus contents in elderly patients with osteoporosis.